212k views
3 votes
How do you solve the problem -6x + 12 = 8 -2x?

User Ravi G
by
4.5k points

2 Answers

6 votes
-6x + 12 = 8 - 2x x = 1
User Ephemerr
by
5.7k points
3 votes

Answer:

Step-by-step explanation: -6x+12=8-2x

One solution was found :

x = 1

Rearrange:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

-6*x+12-(8-2*x)=0

Step by step solution :

Step 1 :

Pulling out like terms :

1.1 Pull out like factors :

-4x + 4 = -4 • (x - 1)

Equation at the end of step 1 :

Step 2 :

Equations which are never true :

2.1 Solve : -4 = 0

This equation has no solution.

A a non-zero constant never equals zero.

Solving a Single Variable Equation :

2.2 Solve : x-1 = 0

Add 1 to both sides of the equation :

x = 1

One solution was found :

x = 1

Processing ends successfully

User Kunchok
by
4.4k points